The Green Entrepreneur - Arafah , Willy (Universitas Trisakti, 2006)
Like a number of other management terms, entrepreneurship is easy to conceptualize but hard to explain. This article aim to investigate theory of green entrepreneur because entrepreneurial do individuals have to play in the adoption of more sustainable business practices. In general, entrepreneurs are individuals who conceive new business opportunities and who take on the risks required to convert those ideas into reality. Traditionally, environmental business management has focused its attention on how and why existing firms can become greener. When this dynamism is applied to developing business solutions that help move enterprise along more sustainable ways, then the results have the potential to be truly fascinating and rewarding.